Detection of Bacterial Contaminants and Identification of Salmonella Sp. in Cilok Snack in Selaparang District, Mataram - Putri, Vita Septiana Sulaiman; Faturrahman, Faturrahman; Sarkono, Sarkono; Tresnani, Galuh; Suryadi, Bambang Fajar (Samota Journal of Biological Sciences, 2023)
Cilok is a boiled snack made from starch with or without a mixture of minced meat, has a savory and chewy taste. Cilok is one of the favorite snacks in Indonesia. Most cilok sellers sell their cilok right on the side of the main road for hours. This allows cilok that are sold to be contaminated with various bacteria. This study aims to calculate the Total Plate Count (TPC) of bacteria and to identify Salmonella sp. in cilok and its sauce in Selaparang District, Mataram City. This study used quantitative method in the form of calculating the TPC of the bacteria and qualitative method in the form of sample isolation on selective media, sugar, and biochemical tests. The results of this study showed that the TPC of the bacteria from the cilok sellers samples number 1 to 8 were 1,2x102, 1x101, 1x101, 2x101, 1,2x102, 1,5x102, 3,9x101, and 3,5x102 cfu/g respectively. Meanwhile, the TPC of the bacteria from sellers' sauce samples number 1 to 8 were 2x102, 1,8x103, 1x101, 1x101, 1,5x101, 7,9x103, 1,7x105 and 1,7x103 cfu/mL, and there was no contamination of Salmonella sp. on cilok nor its sauce samples. All the cilok samples that has been examined had TPC bacterial value that did not exceed the standards set by SNI 7388-2009, so they were still safe for consumption. Meanwhile, one out of eight sauce samples had a bacterial TPC value that exceeded the standard, making it not safe for consumption.